THEORICAL AND PRACTICAL ASPECTS OF LABOR MARKET - Zafar R. Hudayberdiev (Статистика и экономика)
Some aspects of the labor market of Uzbekistan in the condition of the period of economical transition are researched in the paper. Statistic data is used from the beginning of independence period to the present. The evaluation mechanism of the labor market of Uzbekistan is also estimated. The aim of the study was to study the current state of the labor market of Uzbekistan in the condition of a transitional economy, thus to develop theoretical and practical recommendations. To achieve this goals, it was necessary to perform the following task: to determine the factors of influencing the labor market and theoretically substantiating the impact of these factors on the labor market to show its reflection on practice, using the method of scientific abstraction, separately investigate the influence of demographic processes on labor market.